Framing Pemberitaan Diskresi Ahok untuk Reklamasi Jakarta pada Majalah Tempo - Afdiningsih, Fuji Lara Sakti; Sihabudin, H A; Praceka, Puspita Asri (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2017)
This paper examines the additional 15 percent of Basuki Tjahaja Purnama (Ahok) discretion on reclamation for project developers. This paper aims to determine how Ahok’s discretion in Tempo magazine is constructed. The method of framing analysis of Robert N. Entman is employed. The news articles are taken from Tempo Magazine issues of 11 to 17 April 2016, 23 to 29 May 2016, and 20 to 26 June 2016. The sample are 8 news articles. Utilizing the analysis framing model by Robert N. Entman, this paper examines four devices unit of analysis: define problems, diagnose causes, make moral judgments, and treatment recommendation. The paper shows that Tempo is criticizing Ahok discretion. Tempo urges KPK to investigate the accuracy of Ahok discretion, because there is no legal foundation and the source of the problem of bribery reclamation cases. Aguan is suspected to participate in blocking the additional contribution. It is suggested that Tempo should reduce anonymous source in reporting so that the information is more reliable.